Polymer composition for laser marking
By using polymer compositions embedded with composite pigments and titanium oxide or titanate particles in polyamide or polyester plastics, the problem of difficulty in achieving durable, dark, and high-contrast laser lettering in the prior art is solved, and efficient and long-lasting laser lettering effect is achieved.
Patent Information
- Application Number
- CN202380062476.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-07-24
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to achieve long-lasting, dark, high contrast and clear edge laser lettering in polyamide or polyester plastics, especially when flame retardant is included.
A polymer composition is used in which polymer particles are embedded in a carrier polymer matrix formed of polyamide or polyester, which is composed of a sulfur-containing polymer matrix and is uniformly embedded in the composite pigment and titanium oxide or titanate particles.
Achieves long-lasting, dark, high contrast and clear edges in polyamide or polyester plastics, suitable for different laser lettering speeds and reduces odor generation during or after laser action.
Smart Images

Figure BDA0005288749020000201 
Figure BDA0005288749020000211 
Figure BDA0005288749020000221
Abstract
Description
Technical Field
[0001] The invention relates to a polymer composition comprising a carrier polymer matrix formed from polyamide or polyester in which specific polymer particles are embedded, a method for preparing such a polymer composition, its use as a laser writing additive or laser welding additive in an organic polymer composition, and a laser-inscribed or laser-weldable organic polymer composition comprising such a polymer composition. Background Art
[0002] The marking of plastic products has long been a current topic and its importance continues to grow. Although classical marking methods are implemented as above (such as printing, labeling or embossing of intermediate or final products), these methods are more complex in design and are usually defective in terms of the durability of the marking.
[0003] Laser inscription of plastic products has also been practiced for a long time, which can be carried out contactlessly during the continuous production process, produces a permanent mark, can be done without consumables during the actual inscription, and reduces the occurrence of drops and device failures. In this respect, laser inscription has clear advantages over conventional marking methods in terms of materials and technology. Laser marking is very permanent. Since the laser marking takes place within the material, there are no adhesion problems as in the case of labels and direct printing methods.
[0004] Light or dark laser markings of plastics can be produced by different reactions in the plastics.
[0005] The organic matrix of the plastic itself or the added laser additive can then absorb the laser radiation, wherein the energy thus output to the plastic leads to carbonization or foaming of the plastic. In addition, the laser additive contained in the plastic can also react intrinsically to the laser radiation and produce a change in its color (e.g., by darkening) under the influence of the incident laser energy.
[0006] Very few plastics respond very well to a laser beam without additives, while most plastic types typically show only weak markings or no marking at all or respond only to a laser beam of a certain wavelength within a narrow range.
[0007] Thus, without the corresponding addition of laser additives, it is almost impossible to inscribe polyamides, for example, with good contrast using conventional laser equipment, since polyamides can usually only be marked lightly due to their chemical properties. Polyamides usually tend to foam during laser inscription. Technical applications mainly use Nd:YAG lasers or fiber lasers emitting at a wavelength of 1064 nm or 1062-1070 nm. The markings produced by these lasers do not meet market requirements.
[0008] Even in the case of polyester, there is a demand on the market for producing better dark markings. This demand is mainly the result of the use of flame retardants in compounds such as those used in electrical and electronic applications. Flame retardants also lead to stronger foaming and thus prevent dark markings.
[0009] In US 3839064, polymeric microcapsule systems are described which consist of isolated spherical particles, each of which has a polymer core in which inorganic particles are dispersed and a solid polymer shell surrounding the polymer core. These particles have high opacity and influenceable gloss and are used in particular as colorants in fiber-containing products. The core of the microcapsule preferably consists of polystyrene, in which inorganic particles such as titanium dioxide, barium sulfate, calcium carbonate or carbon black may be dispersed. The solid shell preferably consists of hydroxylated polymers such as methylcellulose, polyvinyl alcohol or gelatin. Polyamides can also be used as shell materials. It is not reported whether and how fiber systems containing these particles respond to laser beams.
[0010] In WO 9530716 A1, the molding material based on thermoplastic or thermosetting plastic A) is selected from the group of polyphenylene ether, polyarylene sulfone, polyarylene ether ketone or polyimide, and the plastic contains 0.05 to 10% by weight of micropowder of spherical particles with a substantially smooth surface structure, relative to A), and the micropowder contains at least one polymer B) different from A) as an essential component. Optionally, additives such as bone ash or carbon black may be contained.
[0011] WO 9858805 describes laser-markable plastics which are unique in that the plastics which are difficult to laser-actuate contain an intrinsically laser-markable polymer in the form of micro-ground particles with a particle size of 0.1 to 100 μm as an absorber material. In Example 3, a composition of polyamide 6 (99 parts) and 1 part of polyimide sulfone is described. In Example 4, a composition of polyamide 6 (99.6 parts) and 0.4 parts of polyphenylsulfone is described. In Example 6, a composition of unsaturated polyester resin (99 parts) and 1 part of polyphenylsulfone is described, which contains cobalt octoate and cyclohexanone peroxide as additives. In Example 8, a mixture of 96 parts of polyphenylene sulfide and 4 parts of basic copper sulfate is described, which can be processed into a plastic (for example a polyamide) at 0.4%.
[0012] Laser-absorbing particles are known from WO 2004050766 A1, which particles have as core a first polymer in which an absorbent is contained, wherein a second polymer is bonded via a functional group at the surface of this core, and the first polymer and the second polymer have functional groups that are different from each other. Preferably three polymers are used and optionally four polymers are also used. As absorbents, antimony trioxide, tin dioxide, barium titanate, titanium dioxide, aluminum oxide, copper phosphate and anthraquinone dyes or azo dyes are described as preferred. For the core, polyamides and polyesters are described as preferred. Suitable second polymers are polyolefin polymers that carry special non-functional groups.
[0013] In WO 09090057 a method for producing a laser-markable polymer material is proposed, wherein a base polymer which is difficult to laser-mark and an intrinsically laser-markable sensitive polymer and optionally further polymer materials are mixed, wherein all materials are free of functional groups; this mixture is melted to form a masterbatch material; the masterbatch material is converted into a diluted mixture with a diluent polymer; and the diluted mixture is formed into a laser-markable polymer material by melting the base polymer and the diluent polymer. For example, polyamide 6 is mixed with polyphenylene sulfide, wherein antimony-doped tin oxide can also be processed into it.
[0014] WO 2014206523 A1 describes microspheres which consist of core-shell particles dispersed in a polyolefin matrix as carrier polymer and which contain in the core a mixture of elemental carbon and at least one metal oxide and / or metal titanate as absorber and at least one non-olefin polymer compound as developer, and the shell contains at least one compatibilizer.
[0015] WO 2017016645 A1 describes special composite pigments as laser additives which, similar to conventional industrial methods, can be introduced into the plastic to be marked as a dry pigment mixture, as a liquid preparation or paste or via a plastic or wax-based concentrate (so-called masterbatch).
[0016] US20210388206 A1 describes a polymer-ceramic composite in which a ceramic filler is dispersed in a polymer matrix.
[0017] The use of known laser additives as described above enables usable marking, but does not yet meet market requirements, in particular when colored polyamide or polyester moldings are to be marked, in particular when they additionally contain flame retardants. Therefore, there is also a need for improved laser marking additives or laser welding additives for plastics made of polyamide or polyester, which in the products produced therefrom, when irradiated with the types of lasers commonly used in industry, lead to improved, permanent, dark, high-contrast and sharply defined markings. Laser additives should enable such high-contrast markings for lasers both at lower and higher laser marking speeds.
[0018] Another goal of the product development was to minimize the odor that occurs during or after laser action, which occurs especially when using sulfur-containing polymers.
[0019] It has now been found that the polymer compositions described or preferably described below achieve this object and overcome the disadvantages of the prior art.
[0020] It has thus been shown that such desired laser activity of polyamide or polyester plastics or products produced therefrom with a permanently dark, high-contrast and sharply-margined marking can be achieved when a polymer composition having a carrier matrix formed of polyamide or polyester and containing polymer particles, which, in addition to laser beam-absorbing microparticles, also contain a sulfur-containing polymer which changes color by the laser beam, is added to a polyamide or polyester material to be inscribed or welded. Due to the synergistic effect between the two absorbers and the intrinsically active sulfur-containing polymer, the light-colored polymer composition can be used as a laser additive as described above with improved laser inscription properties with respect to contrast of dark markings (compared to the color of the base material of the plastic to be marked), sharpness of edges and speed (compared to known laser additives). Summary of the invention
[0021] Thus, a first subject of the present invention is a polymer composition comprising a carrier polymer matrix formed from polyamide or polyester, in which polymer particles are embedded, wherein the polymer particles consist of a polymer matrix formed from a sulfur-containing polymer, in which particulate titanium oxide or particulate titanate, which may be doped, and a composite pigment are uniformly embedded, wherein at least 80% by weight of the composite pigment consists of titanium dioxide (TiO 2 ) and antimony-doped tin dioxide ((Sb,Sn)O 2 )composition.
[0022] Further subjects of the invention include a process for preparing the polymer composition, the use of the polymer composition as a laser inscription additive or laser welding additive, and an organic polymer composition capable of laser inscription or laser welding which comprises the polymer composition of the invention.
[0023] In particular, polyamides as carrier matrix polymers for the polymer particles can significantly reduce the development of odors that occur during laser marking.
[0024] Description of the invention
[0025] Laser marking in the sense of the present invention is understood to be any type of marking of plastics and coatings on objects containing these plastics, which can be produced by the action of a laser beam in the form of a label, code, mark, decoration or similar visible change in the appearance of the plastic.
[0026] The abbreviation for polyamide is PA. The term "laser absorbing particles" is used synonymously with "absorber" and "absorbing particles".
[0027] As previously described or preferably described later, the preferred delivery form of the polymer composition according to the invention is granules. Due to its flowability, granules are bulk materials that can be easily transported and can be easily further processed. Alternatively, the delivery form of the polymer composition according to the invention can also be a powder, a flowable material or a paste.
[0028] The polymer composition of the present invention comprises a carrier polymer matrix formed by a polyamide or polyester, wherein the type of polyamide or polyester is not limited. The carrier polymer matrix can be selected from a homopolymer, a copolymer or a polymer blend of polyamide or polyester, which can be linear or branched. Those skilled in the art are not limited in the chemical nature of the polyamide or polyester and can select from a variety of commercial products. Ideally, the polyamide type or polyester type of the carrier polymer matrix is selected to make it compatible with the plastic that should be laser marked.
[0029] In a preferred embodiment of the carrier polymer matrix, the polyamide or polyester has a melting temperature in the range of 160°C to 250°C.
[0030] In a particularly preferred embodiment of the carrier polymer matrix, the polyamide is selected from PA6 or PA12, in particular from PA12. A particularly preferred PA12 is the commercially available product of Evonik Operations GmbH L1600.
[0031] In a preferred embodiment of the carrier polymer matrix, the polyester is selected from polyethylene terephthalate (PET), polyethylene terephthalate-glycol (PETG) or polybutylene terephthalate (PBT).
[0032] Besides the carrier polymer matrix formed from polyamide or polyester in which the polymer particles are homogeneously embedded, the polymer composition according to the invention may also comprise further additives, such as adhesion promoters, stabilizers, fillers or colorants, as described above or preferably explained below.
[0033] For example, thermoplastic polymers carrying functional groups are suitable as adhesion promoters, which include not only terminal groups but also additionally introduced functional groups. Generally, they can be graft copolymers or block copolymers. Suitable adhesion promoters are polymers grafted with maleic anhydride, such as Fusabond from Dow. TM .
[0034] For example, phenolic antioxidants are suitable as stabilizers, such as BASF's 1010 and 1098 and phosphites such as 168.
[0035] For example, various silicates, SiO 2 , talc, kaolin, mica, wollastonite, glass fibers, glass beads, carbon fibers or the like are suitable as fillers.
[0036] As coloring agents, both organic dyes and inorganic or organic pigments are conceivable. Since the polymer composition according to the invention is very light and can therefore be easily colored, virtually all soluble dyes or insoluble pigments suitable for polyamides or polyesters can be used. As an example, only the commonly used white pigment TiO 2 , ZnO, BaSO 4 and CaCO 3 The amount and type of fillers and / or colorants added are known to the person skilled in the art and are limited only by the respective specific material quality of the laser-inscribeable or laser-weldable organic polymer composition into which the polymer composition according to the invention is to be processed for the purpose of use.
[0037] In a preferred embodiment of the polymer composition according to the invention, the polymer composition consists of the carrier polymer matrix, as described above or preferably specified, into which polymer particles are embedded, wherein the polymer particles have the meanings as described above or preferably specified below.
[0038] In a preferred embodiment of the polymer particles embedded in the carrier polymer matrix, as described above, the sulfur-containing polymer of the polymer matrix is selected from polysulfone or polyphenylensulfide.
[0039] The polymer matrix may be selected from homopolymers, copolymers or polymer blends of polysulfones or polyphenylene sulfides, which may be linear or branched. Those skilled in the art are not limited in the chemical nature of polysulfones or polyphenylene sulfides and may select from a variety of commercial products. The term "polysulfone" is used to describe this polymer class, but is also used in combination with the abbreviation PSU as a specific polymer.
[0040] In a particularly preferred embodiment of the polymer matrix, the polysulfone is selected from polysulfone (PSU), polyarylene sulfone (PAS), polybiphenyl sulfone (PSF), polyether sulfone (PES) or polyphenylene sulfone (PPSU). Commercially available from BASF.
[0041] In a particularly preferred embodiment of the polymer matrix for the polymer particles, polyphenylene sulfide (PPS) is selected.
[0042] As stated above or preferably specified, the PPS preferably has a viscosity of 200 to 600 Pa*s, measured in a capillary rheometer according to ISO 11443 at 310° C. and a shear rate of 1200 1 / s.
[0043] As stated above or preferably indicated, PPS particularly preferably has a viscosity of 300 to 500 Pa*s, measured at 310° C. and a shear rate of 1200 1 / s in a capillary rheometer to ISO 11443.
[0044] A particularly preferred commercially available product is Celanese's 0320C0 and 1200L1.
[0045] As described above or preferably illustrated, according to the present invention, two types of laser-absorbing particles are processed into the polymer matrix, which particles subsequently form the polymer particles together with the polymer matrix. The first type of laser-absorbing particles are particulate titanium oxides or particulate titanates, which may be doped, respectively, and the second type are composite pigments, wherein at least 80% by weight of the composite pigment consists of titanium dioxide (TiO 2 ) and antimony-doped tin dioxide ((Sb,Sn)O 2 )composition.
[0046] In general, the person skilled in the art is not limited in the choice of particulate titanium oxide and particulate titanate.
[0047] As described above or preferably illustrated, the particle size of the laser-absorbing particles selected from particulate titanium oxide or particulate titanate is determined by the requirement that the particles must be mixable into the polymer matrix. It is known to those skilled in the art that this miscibility is determined by the total surface area of a certain weight of the laser-absorbing particles, and when the desired size of the polymer particles and the amount of laser-absorbing particles to be mixed are known, the person skilled in the art can determine the lower limit of the particle size without difficulty.
[0048] In a particularly preferred embodiment of the polymer particles, particulate titanium dioxide, which may be doped, is processed into the polymer matrix, as described above or preferably indicated.
[0049] The particulate titanium dioxide can be in the form of rutile or anatase or in an amorphous form, but is preferably present in the form of rutile. The preferred average particle size is in the range of 0.1 to 4 μm, particularly preferably in the range of 0.15 to 2 μm. The particulate titanium dioxide itself can have any conceivable shape. It is preferred that the particulate titanium dioxide has an isotropic shape. This is a shape that is the same in all directions of the core, i.e., there is no preferred direction, when viewed from an imaginary center point, under more or less ideal conditions. This includes spherical and cubic cores as well as cores with irregular compact particle shapes, but also regular or semi-regular polyhedral forms with n faces (Platonic bodies and Archimedean bodies), where n is in the range of 4 to 92.
[0050] It is of course understood that the terms "spherical", "cubic" or "correct" also apply here to core shapes that are not perfectly spherical, perfectly cubic or perfectly correct in the geometric sense. Since the particulate titanium dioxide is produced in a process, process-induced deviations from the ideal geometry (e.g. rounded edges in the case of a tetrahedron or faces of slightly different size and shape) are also included here.
[0051] The titanium dioxide can also be doped. In the sense of the present invention, "doping" is understood to mean the presence of corresponding ions in small amounts as defect sites in the titanium dioxide crystal lattice. Preferred doping is doping with iron or cerium ions. Very particularly preferred is doping of the titanium dioxide with iron ions.
[0052] Particulate titanium dioxide suitable for processing into the polymer matrix according to the invention can be obtained by various methods known to those skilled in the art. For example, it can be prepared by pyrolysis (for example by means of flame pyrolysis), by means of a sol-gel process, by a hydrothermal plasma process or a combination of various process variants.
[0053] However, in another inventive variant it is preferred that the particulate titanium dioxide is not doped. Suitable particulate titanium dioxide of the given magnitude is available, for example, under the trade name (KRONOS Worldwide, Inc.), (Venator) or (Ishihara Corp.). Particularly preferred particulate titanium dioxide is commercially available from KRONOS Worldwide Inc. 2220.
[0054] Salts or esters of titanic acid are referred to as titanates. Alternatively, they can be considered as mixed oxides. The particulate titanates that can be used according to the invention can be of natural origin or synthetically prepared. Titanium minerals of natural origin that can be used as particulate titanates according to the invention are perovskite, barioperowskit, mazedonit, ilmenite, geikielith, ruthenium manganese ore, tausonite, which can be purified and ground accordingly for use.
[0055] In a particularly preferred embodiment of the polymer particles, a particulate titanate selected from aluminum titanate, bismuth titanate, copper titanate, iron titanate, magnesium titanate, potassium titanate, sodium titanate, zinc titanate, cerium titanate, calcium titanate, barium titanate or strontium titanate is processed into the polymer matrix as described above or preferably illustrated. The preferred particulate titanate is aluminum titanate (Al 2 TiO 5 ), sodium titanate (Na 2 TiO 3 ), potassium titanate (K 2 TiO 3 ), zinc titanate (ZnTiO 3 ), calcium titanate (CaTiO 3 ), cerium titanate (CeTiO 4 ), barium titanate (BaTiO 3 ) or magnesium titanate (MgTiO 3 ). Particularly preferred particulate titanates are sodium titanate, potassium titanate, zinc titanate and magnesium titanate.
[0056] Preferably, the average particle size of the particulate titanate described above is in the range from 0.1 to 20 μm, preferably in the range from 0.2 to 15 μm and very particularly preferably in the range from 0.5 to 10 μm.
[0057] Suitable metal titanates are, for example, calcium titanate 99% (d50 max. 3.5 μm) from ABCR GMBH & Co. KG, potassium titanium oxide, magnesium titanium oxide, calcium titanium oxide 99+% from Alfa Aesar, barium titanate 99.9% nanometer (approximately 400 nm; BET 2.3-2.7 μm) from ABCR GmbH & Co. KG. 2 / g).
[0058] In a preferred embodiment of the polymer particles, as described above or preferably illustrated, in addition to the first type of laser-absorbing particles, a composite pigment is processed into the polymer matrix, the composite pigment comprising a titanium dioxide core and at least one coating formed of tin dioxide doped with antimony, and the composite pigment optionally has an outer protective layer and / or a coating between the titanium dioxide core and [(Sb,Sn)O 2 ]One or more intermediate layers between the coating layers.
[0059] If the individual composite pigment particles consist only of a single core and a coating on the core, the composite pigment used according to the invention consists only of a combination of primary particles and is therefore monodisperse. However, more common and therefore preferred is the embodiment in which the composite pigment used is an aggregate of two or more primary particles, each of which has a core and a coating arranged on the core.
[0060] According to the invention, composite pigments can be used whose primary particles have a layer structure of the core / functional layer sequence, a layer structure of the core / intermediate layer / functional layer, a layer structure of the core / functional layer / protective layer or a layer structure of the core / intermediate layer / functional layer / protective layer. The functional layer is a coating formed of tin dioxide doped with antimony.
[0061] Here, the sum of core and functional layer (i.e. TiO 2 The weight proportion of the total of tin oxide doped with antimony and tin dioxide doped with antimony is at least 80% by weight, preferably at least 90% by weight and in particular 95-100% by weight.
[0062] If intermediate layers and / or protective layers are present, they consist predominantly of inorganic materials when they are intermediate layers. Good intermediate layers are metal oxides, in particular SiO 2 SnO 2 、Al 2O 3 、ZnO、CaO、ZrO 2 , Sb 2 O 3 or a mixture thereof.
[0063] In contrast, the protective layer that may be present on the surface of the composite pigment used can be of both inorganic and organic nature. When the use of the composite pigment in the application medium (i.e., in this case, the sulfur-containing polymer matrix) is additionally facilitated by a corresponding surface coating, a protective layer is generally applied. In the case of an inorganic protective layer, the protective layer is preferably ZrO 2 、Ce 2 O 3 Cr 2 O 3 , CaO, SiO 2 、Al 2 O 3 , ZnO, TiO 2 SnO 2 , Sb 2 O 3 Or the corresponding hydrated oxide and a mixture of two or more thereof. The organic protective layer is usually composed of a suitable organosilane, an organic titanate or an organic zirconate. Suitable substances are known to those skilled in the art as agents for surface coating and subsequent surface coating of effect pigments.
[0064] The total weight proportion of the intermediate layer and / or the protective layer is hereby at most 20% by weight, preferably at most 10% by weight, particularly preferably 0 to 5% by weight, relative to the total weight of the composite pigment.
[0065] In a particularly preferred embodiment of the composite pigment, the composite pigment used consists only of TiO 2 and (Sb,Sn)O 2 The minimal amounts of further constituents (0.001 to 0.1% by weight of foreign ions) are only possible due to the nature of the titanium dioxide used or the nature of the tin dioxide doped with antimony.
[0066] In a preferred embodiment of the composite pigment, the coating of tin dioxide doped with antimony consists of a material in which the percentage weight ratio of antimony to tin is between 2 and 35 wt. %, preferably 8 to 30 wt. % and in particular 10 to 20 wt. %, relative to the total weight of antimony and tin.
[0067] In a preferred embodiment of the present invention, the composite pigment to be used according to the invention consists only of one or more primary particles, each of which is composed of a core and a functional layer located on the core, i.e., of TiO 2Core and (Sb,Sn)O 2 However, the most preferred embodiment is the following, wherein the composite pigment is composed of TiO 2 Core and (Sb,Sn)O 2 The coating is composed of primary particles.
[0068] The core itself in the composite pigment used according to the invention can have any conceivable shape. It is preferred that the core in the composite pigment has an isotropic shape. This is a shape that, in more or less ideal conditions, viewed from an imaginary center point, is identical in all directions of the core, i.e. has no preferred direction, as explained above for particulate titanium dioxide. The same explanations regarding the shape also apply correspondingly.
[0069] Since the core of the composite pigment is produced in a process, process-induced deviations from the ideal geometry (eg rounded edges in the case of a tetrahedron or faces of slightly different size and shape) are also included here.
[0070] The core in the composite pigment used according to the invention has a particle size in the range from 0.001 to 10 μm, preferably in the range from 0.001 to 5 μm and in particular in the range from 0.01 to 3 μm.
[0071] These cores are made of TiO2, which is commercially available in the order of magnitude given. 2 Therefore, TiO 2 Particles such as those under the trade name (KRONOS Worldwide, Inc.), (Venator) or (Ishihara Corp.)
[0072] The primary particles of the composite pigments used according to the invention have a coating on the surface of a core having the size and material composition given above, said coating having a layer thickness in the range from 1 to 500 nm, preferably in the range from 1 to 200 nm.
[0073] As already presented above, the coating comprises at least one functional layer. If present, intermediate layers or protective layers are also included in the coating. The above-mentioned orders of magnitude of the layer thickness of the coating relate here not only to coatings consisting only of the functional layer as described above, but also to coatings which, in addition to the functional layer, also have one or more intermediate layers and / or protective layers. Particularly preferred are coatings consisting only of [(Sb,Sn)O 2 ] The layer thickness range of the coating consisting of the functional layer is 1 to 100 nm, as described above or preferably specified.
[0074] The proportion of the coating is 5 to 70% by weight relative to the total weight of the primary particles and likewise 5 to 70% by weight relative to the total weight of the composite pigment. These values relate not only to coatings consisting of only one functional layer as described above, but also to coatings which contain one or more intermediate layers and / or protective layers in addition to this functional layer.
[0075] The composite pigment has a composition of TiO 2 The formed core and the antimony-doped tin dioxide [(Sb,Sn)O 2 ] In a preferred embodiment of the coating, the proportion of the coating is preferably in the range of 35 to 55 wt %, in particular in the range of 40 to 50 wt %, relative to the total weight of the primary particles or relative to the total weight of the composite pigment.
[0076] The particle size of the composite pigment used according to the invention is in the range of 0.1 nm to 10 μm, preferably in the range of 0.2 nm to 5 μm. It is particularly preferred to use a composite pigment having a particle size in the range of 0.1 to 1 μm and D 90 Composite pigments with values ranging from 0.70 to 0.90 μm.
[0077] All particle sizes given above or given below can be determined here using conventional methods for determining particle sizes. Particularly preferred is a method for determining the particle size by laser diffraction, wherein preferably the nominal particle size of the individual particles as well as their percentage size distribution can be determined. All particle size determinations carried out in the present invention were determined by laser diffraction using a Malvern 2000 apparatus from Malvern Instruments Ltd., UK, in accordance with ISO / DIS 13320 standard conditions.
[0078] The layer thickness of the respective coating is determined numerically with the aid of REM images and / or TEM images, as is known to the person skilled in the art.
[0079] The preparation of the composite pigment used according to the invention is carried out according to methods known per se. Here, the titanium dioxide particles used as the core are provided with a coating, as described above or preferably illustrated. Since inorganic materials are used respectively, the coating of the core with the functional layer is preferably carried out in an aqueous suspension by oxidation of the corresponding metal or precipitation of a hydrated metal oxide and subsequent conversion into a metal oxide. Here, the precursor material of the metal oxide to be obtained (generally a metal salt) is added in dissolved form to an aqueous suspension of the corresponding core material and precipitated onto the core (generally in the form of a hydrated metal oxide) at a corresponding set pH value. The hydrated metal oxide is then converted into the corresponding oxide by treatment at high temperature. If it is an inorganic layer, coating the core with an optionally applied intermediate layer and / or protective layer can be carried out in the same manner. The organic subsequent coating is also carried out according to conventional methods in the prior art, in particular by directly contacting the surface of the composite particles with the corresponding organic material in a suitable medium.
[0080] The synthesis of a TiO2 layer with a functional layer of antimony-doped tin dioxide is described in detail in the Examples section (Synthesis Example 1). 2 A preferred embodiment of the preparation of composite pigments consisting of a core. A particularly preferred composite pigment for use according to the invention is Iriotec Name Commercially available.
[0081] In a preferred embodiment of the polymer particles used as a component of the polymer composition of the present invention, as described above or preferably illustrated, relative to the composite pigment, as described above or preferably illustrated, the percentage weight ratio of the particulate titanium oxide or particulate titanate relative to the total weight of the particulate titanium oxide or particulate titanate and the composite pigment is 50 to 99 weight %, as described above or preferably illustrated.
[0082] Preferably, in this embodiment of the polymer particles used as a constituent of the polymer composition of the present invention, relative to the composite pigment, as described above or preferably specified, the percentage weight ratio of the particulate titanium oxide or particulate titanate relative to the total weight of the particulate titanium oxide or particulate titanate and the composite pigment is 60 to 97.5% by weight, particularly preferably 70 to 95% by weight, as described above or preferably specified.
[0083] The described laser-absorbing particles (whose composition and their percentage weight ratios relative to each other, for example, as previously described or preferably described) are contained in the sulfur-containing polymer matrix in an amount of 5 to 90 weight %, preferably 10 to 80 weight %, and in particular 30 to 70 weight %, relative to the total weight of the sulfur-containing polymer matrix and the laser-absorbing particles constituting the polymer particles, respectively.
[0084] The particle size of the polymer particles formed during the preparation of the polymer composition of the invention and used as a constituent of the polymer composition of the invention is in the range of 0.5 to 50 μm, preferably 1 to 20 μm and in particular 2 to 10 μm. The size of the polymer particles can be determined by investigation in REM / TEM.
[0085] Advantageously, the particles are significantly smaller than 50 μm, since this allows good resolution to be achieved during laser marking.
[0086] When preparing the polymer composition of the present invention, the preparation of the polymer particles is carried out in situ. Precursors suitable for the in situ preparation of the polymer particles are described in the process below.
[0087] In a suitable method, first, particulate titanium oxide or particulate titanate is mixed with a composite pigment while maintaining the given weight ratio as described above or preferably described, and a solid mixture is obtained. Any mixer, such as a drum mixer, can be used for this purpose. The powder mixture is then uniformly mixed with a sulfur-containing polymer as described above or preferably described and extruded into a precursor and cured under the described weight ratio. The term "extrusion" is also known in the professional field and means that a curable substance is pressed out through an opening. For this purpose, an extruder is used according to the present invention. In the professional field, extruders are also known and commercially available. The term extruder represents a conveying device for performing extrusion. For example, a single-screw extruder or a twin-screw extruder can be used. Due to the corresponding method process tasks (such as feeding, conveying, homogenization, softening and compression), the selection and adaptation of a suitable extrusion screw, especially the selection and adaptation of its geometry, belongs to the general knowledge of those skilled in the art. Preferably, a powder mixture of laser-absorbing particles and a certain amount of sulfur-containing polymer in powder form, flowable material form and / or as pellets are mixed in a co-rotating twin-screw extruder, wherein the mixture is melted in the extruder and sheared strongly to ensure uniform distribution, and then extruded and solidified. It can be proposed that the powder mixture of laser-absorbing particles and the sulfur-containing polymer are added to two different inlets at the same time or added alternately in succession or added in succession or added to a single inlet at the same time. The production of the precursor is preferably carried out at a temperature higher than the melting point of the sulfur-containing polymer, preferably at a temperature between 280°C and 320°C. Typically, the extrudate is granulated in the rod drawing method. For example, the mixture to be solidified from the extruder is discharged through a perforated plate. The melt rod is then cooled in a water bath and processed into pellets by a rotating knife. A typical perforated plate has a nozzle of 1-2mm.
[0088] In the next step, the precursor is mixed with a carrier polymer (i.e., a polyamide or polyester). The mixture is then re-compounded on an extruder, wherein a co-rotating twin-screw extruder is again used in a preferred embodiment. Again, the processing temperature must be higher than the melting temperature of the sulfur-containing polymer, preferably a temperature between 280° C. and 320° C. Due to the high shear in the extruder, polymer particles consisting of a sulfur-containing polymer containing two absorbent particles are formed, as previously described. The melt is then passed through a perforated plate and formed into rods, which are then processed into pellets in a rod drawing method by a rotating knife. The resulting product can be used for laser marking and has the optimal properties already mentioned.
[0089] The in situ prepared polymer particles as described above or preferably specified are contained in an amount of 10 to 90 wt.-%, preferably 20 to 80 wt.-% and in particular 30 to 70 wt.-%, respectively, relative to the total weight of the polymer composition, in a carrier polymer matrix formed from polyamide or polyester as described above or preferably specified.
[0090] In the in-situ preparation of the polymer particles as described above or preferably illustrated, the corresponding precursor can also be used for the polymer composition of the present invention comprising the carrier polymer matrix as previously described with a mixture of other additives known in the prior art. In the latter case, the ratio of the precursor is reduced by the ratio of the other additives. The ratio of other additives in the polymer composition of the present invention amounts to 0 to 40 % by weight, particularly preferably 0.1 to 25 % by weight, very preferably 0 to 10 % by weight. Suitable additives have been previously described.
[0091] In a preferred embodiment of the present invention, the polymer composition of the present invention is a polymer composition in which each component corresponds to the preferred embodiment.
[0092] In a particularly preferred embodiment of the present invention, it relates to a polymer composition comprising a carrier polymer matrix formed of polyamide, in which polymer particles are embedded, wherein the polymer particles consist of a polymer matrix formed of polyphenylene sulfide, in which composite pigments and undoped particulate titanium dioxide are uniformly embedded, wherein the composite pigment consists of TiO 2 The core is provided with a functional coating formed of tin dioxide doped with antimony.
[0093] In a particularly preferred embodiment of the present invention, it relates to a polymer composition comprising a carrier polymer matrix formed of polyester, in which polymer particles are embedded, wherein the polymer particles consist of a polymer matrix formed of polyphenylene sulfide, in which composite pigments and undoped particulate titanium dioxide are uniformly embedded, wherein the composite pigments consist of TiO 2The core is provided with a functional coating formed of tin dioxide doped with antimony.
[0094] The same applies correspondingly to the embodiments with regard to the preferred polymers and the laser-absorbing components and their weight ratios relative to one another for this particularly preferred embodiment of the invention.
[0095] According to the previous embodiment, another subject of the present invention is a method for preparing a polymer composition, as described above or preferably specified, characterized in that (i) in a first method step, particulate titanium oxide or particulate titanate and composite pigment are mixed with each other while maintaining the weight ratios given as described above or preferably specified, (ii) in a second method step, this solid mixture from (i) is mixed with a sulfur-containing polymer with each other and uniformly to form a powder mixture, (iii) in a third method step, the powder mixture is plasticized and homogenized and forms a precursor for polymer particles to be produced in situ, and (iv) in a fourth method step, the precursor for polymer particles to be produced in situ from step (iii) is uniformly extruded or solidified together with a carrier polymer matrix formed by polyamide or polyester.
[0096] Method steps (i) to (iii) can be carried out in one apparatus and method step (iv) can be carried out in a second apparatus or can be carried out in the same apparatus at a different point in time. However, it is also possible to carry out all method steps in an extruder.
[0097] Method step (i), method steps (ii) and (iii) and method step (iv) can be carried out in a time-staggered manner, and the intermediate products from these method steps can be stored accordingly until further use. The corresponding storage conditions are known to those skilled in the art.
[0098] In a preferred embodiment of the process for producing the polymer composition according to the invention, the third and / or fourth process step is melt extrusion.
[0099] Another subject of the present invention is an alternative process for producing a polymer composition, as described above or preferably specified, characterized in that (i) the particulate titanium oxide or particulate titanate is metered directly on the extruder with the composite pigment and with the sulfur-containing polymer, maintaining the weight ratios given above or preferably specified, and the precursor for the polymer particles to be produced in situ is formed, and (ii) in a second process step, the precursor for the polymer particles to be produced in situ from step (i) is homogeneously extruded or solidified together with a carrier polymer matrix formed from polyamide or polyester.
[0100] In a preferred embodiment of the alternative process for preparing the polymer composition according to the invention, the two process steps are melt extrusion.
[0101] The pellets of the polymer composition of the invention obtained according to a preferred embodiment preferably have a diameter in the range of 0.1 to 5 mm, preferably 2 to 3 mm, measured optically as an arithmetic mean. The pellets preferably obtained preferably have a diameter in the range of 0.1 to 5 mm, preferably 2 to 3 mm, measured according to the sieve method, wherein at least 90% of the pellet particles, particularly preferably at least 99% of the pellet particles, exhibit a diameter in the range of 0.1 to 5 mm, preferably 2 to 3 mm, wherein the percentage values are based on the number of particles.
[0102] In the case of non-spherical granules, the above-mentioned diameters relate to the smallest extended dimension of the granule particles.
[0103] A further subject matter of the present invention relates to the use of a polymer composition as described or preferably illustrated above as a laser inscription additive or laser welding additive in an organic polymer composition.
[0104] The term "plastic to be marked" in the sense of the present invention is synonymous with "organic polymer composition to be marked".
[0105] Another subject of the invention is a laser-inscribeable or laser-weldable organic polymer composition comprising a carrier polymer matrix of polyamide or polyester in which polymer particles are embedded, wherein the polymer particles consist of a polymer matrix formed from a sulfur-containing polymer in which particulate titanium oxide or particulate titanate, which may be doped, and a composite pigment are uniformly embedded, wherein at least 80% by weight of the composite pigment consists of titanium dioxide (TiO 2 ) and antimony-doped tin dioxide [(Sb,Sn)O 2 ] composition, as described or preferably illustrated above.
[0106] The polymer compositions according to the invention which comprise a carrier polymer matrix formed from polyamide are particularly suitable for processing into plastics to be marked which are compatible with polyamide.
[0107] The polymer compositions according to the invention which comprise a carrier polymer matrix formed from polyester are particularly suitable for processing into plastics to be marked which are compatible with polyester.
[0108] As described above or preferably illustrated, the processing of the polymer composition of the invention as a laser inscription additive or laser welding additive into the plastic to be marked is carried out according to conventional methods known to the person skilled in the art, for example by mixing and optionally deforming under the action of heat.
[0109] The preparation of the organic polymer composition to be marked is carried out, for example, as follows: an organic polymer (for example polymer granules) is mixed with the polymer composition of the invention as a laser inscription additive or laser welding additive and eventually further additives (for example adhesion promoters, stabilizers, flame retardants, fillers or colorants) in a suitable mixer.
[0110] The coloring of plastics is usually carried out via color concentrates (masterbatches) or compounds.
[0111] The mixture thus obtained can then be processed directly in an extruder or injection-casting machine. The molded bodies obtained in such processing show a very uniform distribution of the laser lettering additive or laser welding additive. The extrudate obtained can be further converted into any plastic molded body and can be laser marked. Subsequently, the molded bodies, foils or coatings on objects prepared by injection molding can be subjected to the usual marking processes with suitable lasers.
[0112] Adding the laser lettering additive or the laser welding additive to the plastic material can be carried out simultaneously or successively. When adding the laser additive, adhesion promoters and stabilizers can be optionally added to the plastic material, preferably plastic granules.
[0113] The laser inscription additive or laser welding additive according to the invention is added to the organic polymer or plastic provided for laser marking in a proportion of 0.1 to 30% by weight, preferably 0.5 to 20% by weight and very particularly preferably 1 to 10% by weight, based on the weight of the plastic to be marked.
[0114] A further subject matter of the invention is therefore a laser-inscribeable or laser-weldable organic polymer composition, characterised in that the proportion of the inventive laser inscription additive or laser welding additive is 0.1 to 30% by weight, relative to the weight of the organic polymer composition.
[0115] For laser marking of plastics or plastic-containing coatings on objects, solid-state lasers or fiber lasers with wavelengths of 355 nm (UV), 534 nm (green laser) and 1064 nm or 1062 nm (NIR laser; NIR=near infrared) are typically well suited.
[0116] Pulsed solid-state lasers or fiber lasers with a wavelength of 1064 nm or 1062 nm have proven to be particularly suitable, for example solid-state lasers composed of Nd:YAG single crystals or Nd:yttrium vanadate single crystals with an emission wavelength of 1064 nm or fiber lasers with an emission wavelength of 1064 / 1062 nm.
[0117] The laser markings produced can generally be used whenever a hard-wearing, very dark and sharp-edged marking is to be produced on light-colored or dyed plastics. Application examples are, by no means exhaustive, operating panels or instrument panels in the motor vehicle and aircraft industry, in electrotechnology / electronics and in mechanical and plant engineering; labels or markings for devices, appliances and consumer articles (e.g. washing machines, coffee machines, smartphones or televisions); logos for all types of devices, for containers, toys or tools, type designations or individual markings and decorative markings, especially in the field of advertising.
[0118] The invention is explained below with the aid of exemplary embodiments, but the invention is not restricted to these exemplary embodiments. DETAILED DESCRIPTION
[0119] Example
[0120] Preparation of composite pigments:
[0121] 100 g of approximately spherical TiO with an average particle size in the range of 100-300 nm (measured under standard conditions by laser diffraction using a Malvern 2000 measuring instrument from Malvern Ltd., UK) was added. 2 The particles (Kronos 2900, a product of KRONOS Inc.) were heated to 75° C. in 2 1 of demineralized water with stirring. The pH of the suspension was adjusted to a value of 2.0 with 10% hydrochloric acid. Then, 264.5 g of 50% SnCl 4 solution, 60.4 g of 35% SbCl 3 A hydrochloric acid tin-antimony chloride solution consisting of a solution and 440 g of 10% hydrochloric acid is slowly metered in, wherein the pH value of the suspension is kept constant by simultaneously slowly adding 32% sodium hydroxide solution. After complete addition, stirring is continued for 15 minutes. The pH value is then adjusted to a value of 3.0 by adding 32% sodium hydroxide solution and stirring is continued for 30 minutes.
[0122] The product was filtered, washed, dried, annealed at 500-900°C for 30 minutes and sieved through a 50 μm mesh.
[0123] The obtained particles have a particle size in the range of 0.1 to 1.7 μm and D 50 The value is 0.18 μm and D 90 The value of TiO is 0.74 μm 2 and (Sb,Sn)O 2 The composite pigment formed has a lighter gray-green body color. The ratio of Sn:Sb in the coating is 85:15.
[0124] Preparation of laser additives:
[0125] The following application materials were used to prepare the polymer compositions of the present invention as well as comparative examples.
[0126] As absorbent particles:
[0127] A-1: 2220 - Titanium Dioxide from Kronos
[0128] A-2: 8850 - composite pigment corresponding to the above example - from Merck KGaA
[0129] A-3: 8815 - Antimony Tin Oxide from Merck KGaA
[0130] A-4: 8820 - Antimony tin oxide, titanium dioxide on mica from Merck KGaA
[0131] A-5: 8841 - Basic copper phosphate (90%) + antimony tin oxide (10%) from Merck KGaA
[0132] The absorbent particles used in each case are labeled as absorbent 1 and / or absorbent 2 in Table 1.
[0133] As matrix polymer: M-1: 1200L1-PPS: PPS by Celanese
[0134] As carrier polymer: T-1: L 1600 - PA12 by Evonik
[0135] As test polymer: P-1: B3K-BASF's PA6
[0136] Seat Test Pigment: PP-1: Preparation of Titanium Dioxide Precursor of 2220-KRONOS:
[0137] Various precursors were prepared by means of a twin-screw extruder (Leistritz Mikro 27, screw diameter 27mm, length 36D). The composition of the precursor is shown in Table 1. In the case of using two absorbents, a premix of the two powdered absorbent particles and the pre-ground matrix polymer was first prepared in a drum mixer. The material was then added to the main hopper of the extruder and extruded. Here, the worm rotation speed was 250 rpm. The throughput for all compounding materials was 12 kg / h. The temperature in zone 1 to zone 10 was 290° C. and was also 290° C. at the extrusion head. The material was extruded into rods through a perforated plate with two nozzles of 2 mm in diameter, cooled by a water bath and then cut into cylindrical pellets by a rotating knife.
[0138] Table 1: Preparation of precursors for later in-situ preparation of polymer particles; weight proportions in brackets are in weight percent
[0139]
[0140] Preparation of laser marking concentrates, i.e. comprising polyamide as carrier polymer and the precursors according to Table 1 prepared in situ The composition of the polymer particles
[0141] A series of laser marking concentrates K-1 to K-6 were prepared with the same extruder (Leistritz Mikro 27, screw diameter 27 mm, length 36D). The compositions are presented in Table 2. For this purpose, the precursor and carrier polymer were mixed in a drum mixer and added via the main hopper of the extruder. The screw rotation speed was 250 revolutions per minute and the throughput was 15 kg / h. The temperature in zone 1 was 320° C. and in zone 10 was 300° C. and at the extrusion head was 300° C. The exiting melt was processed into pellets by rod drawing as described above. The laser marking concentrates are referred to as "concentrates" in Table 2 and in the other examples.
[0142] Table 2: Preparation of laser marking concentrates; weight ratios in brackets are in weight percent
[0143]
[0144] * indicates according to the present invention
[0145] Making laser-markable plastics
[0146] Laser-markable polyamides were prepared by extrusion on a twin-screw extruder (LabTech, screw diameter 16 mm, length 40D). The compositions of laser-markable polyamides are shown in Tables 3a and 3b. The laser-marked concentrate according to Table 2 was mixed with the test polymer and optionally with the test pigment in a drum mixer and the mixture was added via the main hopper of the extruder. The screw rotation speed was 400 rpm and the throughput was 4 kg / h. The temperature in zone 1 was 260 ° C, 250 ° C in zone 10 and at the extrusion head. Rods were produced via an orifice plate with a nozzle of 2 mm diameter. The rods were cooled in a water bath and pelletized via a rotating knife.
[0147] In the case of the laser-markable plastics in Table 3a, the corresponding laser-marking concentrates were tested in the test polymers. The laser-markable plastics in Table 3b represent mixtures of carrier polymers with titanium dioxide as the test pigment. The plastics according to Table 3 make it possible to score the performance of the materials in covering formulations. This is therefore important, since the application of the laser additives according to the invention is usually carried out in covering, highly filled systems. The laser-markable plastics are referred to as "compounds" in Tables 3a and 3b.
[0148] Table 3a: Preparation of laser-markable plastics; the weight proportions in brackets are in weight percent
[0149]
[0150] * indicates according to the present invention
[0151] Table 3b: Preparation of laser-markable plastics colored with the test pigments; the weight proportions in brackets are in percent by weight Comparison
[0152] mixture <![CDATA[C-7 * ]]> C-8 Concentrates K-1[2] K-5[2] Testing Pigments PP-1[2] PP-1[2] Test polymer P-1
[96] P-1
[96]
[0153] * indicates according to the present invention
[0154] In the following, the laser-markable plastics C-1 to C-8 were processed into small plates by injection molding on an Arburg Allrounder 320D. The small plates had dimensions of 60x90x1.5 mm and a smooth surface. The injection molding temperature corresponded to the predetermined value for the test polymer P-1. The heating zone was correspondingly set to 260° C. The small plates were used to verify the laser marking.
[0155] Laser Tag Scoring:
[0156] The laser marking is verified with the aid of a Trumpf VMc5 12 Watt vanadate-IR laser system. First, a so-called test grating is marked. In such a test grating, the marking speed (v [mm / s]) and frequency (f [kHz]) are varied at a predetermined power (p [%]). The focus is set exactly to the material surface and the linear distance is a constant 50 μm. The power is set to a constant 100%. The speed is between 500 and 5000 mm / s. The frequency is between 20 and 100 kHz. Such a test grating is essentially used for a first scoring of the marking contrast that can be achieved under optimal laser conditions. In a second step, a solid rectangle with dimensions of 5 cm x 3 cm is lasered onto another small plate. The laser power is 100% here. The marking speed is 3000 mm / s and the frequency is 80 kHz. The line spacing is 50 μm.
[0157] The laser marked rectangular area and the color of the small plate were then measured using a color spectrophotometer Minolta CR-400 according to CIE laboratory. The marking contrast was obtained from the difference between the L value of the small plate color and the L value of the marking.
[0158] Particularly high values represent good marking contrast.
[0159] Table 4a: Laser-markable plastics C-1 * and ratings from C-2 to C-6
[0160]
[0161] * indicates according to the present invention
[0162] Table 4a clearly shows that only the laser-markable plastic C-1 according to the invention with the polymer composition K-1 according to the invention comprising M-1, A-1, A-2 and T-1 has the desired properties. A particularly high marking contrast is shown.
[0163] The two laser-markable plastics comprising the individual components (C-2 comprising only A-1 and C-3 comprising only A-2) lag significantly behind the properties of the mixture. The other comparative examples (C-4 comprising pure antimony tin oxide A-3, C-5 comprising the composite pigment without the titanium dioxide core A-4, and C-6 comprising basic copper phosphate A-5) also lag significantly behind in performance.
[0164] Table 4b: Laser markable plastic C-7 pigmented with test pigments * and C-8 rating
[0165] mixture <![CDATA[C-7 * ]]> C-8 L value of small plate 89.4 82.2 L value of laser marking 54.3 52.6 Marking contrast 35.1 29.6
[0166] * indicates according to the present invention
[0167] Table 4b clearly shows that the pigmented laser-markable plastic C-7 containing the laser concentrate K-1 according to the invention offers advantages in terms of neutral color of the test plaque in combination with a very dark laser marking. This results in the desired high marking contrast.
[0168] According to this, the inventive laser marking additive K-1 can be counterstained more simply than the comparative additive K-5, which meets an important market requirement.
[0169] If used instead of T-1, BASF The results of laser marking showed that the carrier polymer formed by B3K-PA6 was the same as that of the concentrate of the present invention (replacing K-1 * , with PA6) have the same advantages over the comparative concentrates (with PA6 instead of K-2 to K-6).
Claims
1. A polymer composition comprising a carrier polymer matrix consisting of polyamide or polyester, in which polymer particles are embedded, wherein the polymer particles consist of a polymer matrix, which is formed by a sulfur-containing polymer, in which are uniformly embedded: particulate titanium oxide or particulate titanate, which can be doped respectively, and a composite pigment, wherein at least 80% by weight of the composite pigment, relative to the total weight of the composite pigment, consists of titanium dioxide (TiO2) and tin dioxide doped with antimony ((Sb,Sn)O2).
2. The polymer composition according to claim 1, characterized in that The polyamide or polyester has a melting temperature in the range of 160 to 250°C.
3. The polymer composition according to claim 1 or 2, characterized in that The polyamide is PA6 or PA12.
4. The polymer composition according to claim 1 or 2, characterized in that The polyester is polyethylene terephthalate (PET), polyethylene terephthalate-glycol (PETG) or polybutylene terephthalate (PBT).
5. The polymer composition according to one or more of claims 1 to 4, characterized in that The sulfur-containing polymer is polysulfone or polyphenylene sulfide.
6. The polymer composition according to claim 5, characterized in that The polysulfone is selected from polysulfone (PSU), polyarylene sulfone (PAS), polybiphenyl sulfone (PSF), polyether sulfone (PES) or polyphenylene sulfone (PPSU).
7. The polymer composition according to one or more of claims 1 to 6, characterized in that The particulate titanium oxide is particulate titanium dioxide which may be doped.
8. The polymer composition according to one or more of claims 1 to 6, characterized in that The granular titanate is aluminum titanate, bismuth titanate, copper titanate, iron titanate, magnesium titanate, potassium titanate, sodium titanate, zinc titanate, calcium titanate, cerium titanate, barium titanate or strontium titanate.
9. The polymer composition according to one or more of claims 1 to 8, characterized in that The composite pigment comprises a titanium dioxide core and at least one coating formed of tin dioxide doped with antimony, and the composite pigment optionally has an outer protective layer and / or one or more intermediate layers between the titanium dioxide core and the (Sb,Sn)O2 coating.
10. The polymer composition according to claim 9, characterized in that The coating of tin dioxide doped with antimony consists of a material in which the weight ratio of antimony to tin is between 2 and 35% by weight, relative to the total weight of antimony and tin.
11. The polymer composition according to one or more of claims 1 to 10, characterized in that The weight ratio of the particulate titanium oxide or particulate titanate to the composite pigment is between 50 and 99 weight % relative to the total weight of the particulate titanium oxide or particulate titanate and the composite pigment.
12. Process for preparing a polymer composition according to one or more of claims 1 to 11, characterized in that (i) in a first method step, the particulate titanium oxide or particulate titanate and the composite pigment are mixed with one another, (ii) in a second method step, this solid mixture from (i) is mixed with a sulfur-containing polymer and mixed with one another and homogeneously to form a powder mixture, (iii) in a third method step, the powder mixture is plasticized and homogenized and forms a precursor for polymer particles to be produced in situ, and (iv) in a fourth method step, the precursor for polymer particles to be produced in situ from step (iii) is homogeneously extruded or solidified together with a carrier polymer matrix composed of polyamide or polyester.
13. Process for preparing a polymer composition according to one or more of claims 1 to 11, characterized in that (i) the particulate titanium oxide or particulate titanate is metered directly with the composite pigment and with the sulfur-containing polymer on an extruder and forms a precursor for polymer particles to be prepared in situ, and (ii) in a second process step, the precursor for polymer particles to be prepared in situ from step (i) is homogeneously extruded or solidified together with a carrier polymer matrix composed of polyamide or polyester.
14. Use of the polymer composition according to one or more of claims 1 to 11 as a laser writing additive or laser welding additive in organic polymer compositions.
15. Laser-inscribed or laser-weldable organic polymer composition comprising a polymer composition according to one or more of claims 1 to 11.
16. The laser-engravable or laser-weldable organic polymer composition according to claim 15, characterized in that: The proportion of the polymer composition according to one or more of claims 1 to 11 is 0.1 to 30% by weight, relative to the weight of the organic polymer composition.
Citation Information
Patent Citations
Polymer-ceramic composite articles with low dissipation factor and high dielectric constant, and core-shell particle powders and processes for making such articles
US20210388206A1
Inorganic pigment-loaded polymeric microcapsular system
US3839064A
Easily writable thermoplastic moulding materials
WO1995030716A1
Plastics which can be laser-marked
WO1998058805A1
Laser light absorbing additive
WO2004050766A1